Experimental evolution of aging, growth, and reproduction in fruitflies - Stearns, S. C. (The National Academy of Sciences, 2000)
We report in this paper an evolutionary experiment on Drosophila that tested life-history theory and the evolutionary theory of aging. As theory predicts, higher extrinsic mortality rates did lead to the evolution of higher intrinsic mortality rates, to shorter lifespans, and to decreased age and size at eclosion; peak fecundity also shifted earlier in life. These results confirm the key role of extrinsic mortality rates in the evolution of growth, maturation, reproduction, and aging, and they do so with a selection regime that maintained selection on fertility throughout life while holding population densities constant.